2014
DOI: 10.13005/bbra/1291
|View full text |Cite
|
Sign up to set email alerts
|

Xylitol Production from Water Hyacinth (Eichhornia crassipes) by Candida tropicalis Y-27405

Abstract: This is the study which reported the use of, Water hyacinth (Eichornia crassipes) for xylitol production. In this study a simple reliable and efficient hydrolysis by dilute acid hydrolysis using 2% (v/v) H 2 SO 4 was carried out at 121 0 C for 60 min. The acid pretreatment was concentrated under vacuum using rotavapor and further detoxified using overliming and subsequent activated charcoal treatment. The sugars achieved after concentration and detoxification (50±0.3g/l) was subjected to xylitol fermentation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Different studies reported the yield of xylose from E. crassipes biomass. Kalhorinia et al (2014) reported a yield of 35 g/L of xylitol using simple and efficient acid pretreatment, while 0.25 g/L of xylitol was produced from the hemicellulosic parts of the plant by acid hydrolysis (Shankar et al, 2020). The worldwide market of xylitol is more than 700 million USD/year in the food and pharmaceutical industries and is expected to reach 1.37 USD billion by 2025.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Different studies reported the yield of xylose from E. crassipes biomass. Kalhorinia et al (2014) reported a yield of 35 g/L of xylitol using simple and efficient acid pretreatment, while 0.25 g/L of xylitol was produced from the hemicellulosic parts of the plant by acid hydrolysis (Shankar et al, 2020). The worldwide market of xylitol is more than 700 million USD/year in the food and pharmaceutical industries and is expected to reach 1.37 USD billion by 2025.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Adanikin, et al, 2017 reported this to be as a result of the higher crude fiber content in water hyacinth (20.2 per cent, Ogunwande, et al, 2015) compared to that of the morning glory flower. Also, the water hyacinth plant also has a conspicuous amount of cellulose and hemicellulose content which shackles its biodegradation (Manivannan and Narendhirakannan, 2014), organic acids like Luvulinic acid (Lenora et al, 2016), bioethanol (Gunja et al, 2016), biobutanol (Park et al, 2016), biopolymer (Preethi and Umesh, 2015), carbon fiber, composite (Ramirez et al, 2015), biofertilizers (Vidya and Girish, 2014), fish feed/animal feed (Mohapatra, 2015), mushroom cultivation (Onchonga et al, 2013), high calorific fuel (Lu et al, 2016), fuel briquette (Rezania et al, 2015), superabsorbent polymer (Pitaloka et al, 2013), xylitol (Kalhorinia, et al, 2014), vermicompost (Blessy and Prabha, 2014) and even super capacitor electrodes (Kurniawan et al, 2015). This is of course, not considering its other uses, as those other either as medicinal plants (Delphine et al, 2015).…”
Section: Further Review On Production Of Biogas From Decomposable Wastementioning
confidence: 99%